Family economic situation and the level of professional burnout among nurses - Cegła, Bernadeta; Dowbór-Dzwonka, Aneta; Filanowicz, Małgorzata; Szynkiewicz, Ewa; Kędziora-Kornatowska, Kornelia; Bartuzi, Zbigniew (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Professional burnout, also known as the chronic fatigue syndrome, is a state of physical, emotional and mental exhaustion caused by work. This phenomenon can be mainly observed among professionals who, due to the jobs performed, are involved in interactions with other human beings. This problem greatly affects nurses. Aim of the study. The aim of this research was to determine whether financial situation of the family, its size and nurses’ earnings influence the level of professional burnout among nurses. Material and methods. The study group comprised of 252 nurses working in 3 hospitals in the city of Bydgoszcz. Maslach Burnout Inventory (MBI) by Christina Maslach served as the research tool. Results. Results analysis indicated that professional burnout among nurses who do not have children was the highest and amounted to 2.02. In groups of nurses who have one, two, three or more children, the level of burnout was respectively 1.83; 1.82; 1.79. It has also been observed that the level of burnout among professionally active nurses was higher in groups where respondents admitted poor financial situation and amounted to 2.15. In groups of nurses who declared good financial situation the level was 1.54. Similarly, in groups of nurses whose earnings (according to themselves) were very low, the level of professional burnout was 2.38 and among nurses who described their earnings as medium, the level was 1.62. Conclusions. Family’s size and its material status influence the level of professional burnout. Financial situation in nurses’ families influences the level of professional burnout. The occurrence of professional burnout syndrome among nurses depends on the level of their earnings. Nursing Topics 2010; 18 (4): 393-398